From autarky to free trade: The impact on environment - Shlomo Weber; Hans Wiesmeth (Fondazione Eni Enrico Mattei (FEEM), 2001)
We consider a model with two countries, two commodities and production factors, labour and environment. The countries first choose their environmental standards and then the equilibrium market allocations are determined. We study a subgame perfect Nash equilibrium of this game for two types of environmental problems: regional and international. We examine effects resulting from the transition from autarky to free trade and show that regulating interference with supply and demand may have a positive effect on environmental standards. In particular, a transfer of commodity from one country to the other can increase welfare and raise environmental standards in both countries.
Keywords: F18; C72; 330; Free trade; autarky; environmental standards; international and regional environmental problems; Autarkie; Freihandel; Umweltstandard; Umweltbelastung; Theorie